DNA methylation changes and evolution of RNA-based duplication in Sus scrofa: based on a two-step strategy. (February 2018) - Fang, Chengchi; Zou, Cheng; Fu, Yuhua; Li, Jingxuan; Li, Yao; Ma, Yunlong; Zhao, Shuhong; Li, Changchun
Aim: This study aims to couple DNA methylation changes and evolution of retrogenes.Materials & methods: A new two-step strategy was developed to screen retrogenes. Further, reduced representation bisulfite sequencing and RNA-seq data of eight tissues were used to analyze retrogenes.Results: A total of 964 retrocopies were identified and new retrocopies were available for the synthesis of glycans and lipids corresponding to pig phenotypic traits. Retrogenes were consistently hypermethylated. Hypomethylation of parental genes presented more susceptibility to retroposition. Promoter DNA methylation of retrogenes was negatively correlated with evolutionary time and played important roles in regulating retrogene tissue-specific expression pattern.Conclusion: A two-step procedure is effective and necessary for identifying retrogenes. DNA methylation drives origination, survival, evolution and expression of retrogenes.